An anchor node selection mechanism-based node localisation for mines using wireless sensor networks. (18th February 2020) - Li, Kangshun; Wang, Hui; Huang, Ying
To improve the low localisation accuracy problem facing wireless sensor network (WSN) nodes in mines, a localisation algorithm is proposed to improve the localisation accuracy of received signal strength indication (RSSI) using an anchor node selection mechanism. This localisation mainly includes three phases: first, the anchor node RSSI values received from an unknown node are sorted from high to low; second, the four anchor nodes with the highest RSSI values are selected by a Gaussian elimination method. These nodes are not in the same plane and form a prismatic shape, and the distance from any one node to a plane consisting of another three points is not less than a certain threshold value; finally, the square method is used to estimate the coordinates of the unknown nodes to realise the precise localisation of the unknown nodes. The simulation results show that the proposed algorithm has greatly improved the localisation accuracy compared with other traditional localisation algorithms.